Actinopterygii, Siluriformes, Loricariidae, Hypostomus aspilogaster (Cope, 1894) : Distribution extension and first record for Argentina - Cardoso, Yamila Paula (2011)
The present work extends to Argentina the distribution of Hypostomus aspilogaster originally described from Uruguay River in southern Brazil. The examined specimens were sampled in the stream Mandisoví Grande, affluent of Uruguay River in Entre Ríos province, and in Punta Lara, from Río de la Plata basin, in Buenos Aires province, Argentina. This represents the first country record for this species.